The sanctuary of San Miguel de Aralar: religious and intangible heritage on a sacred basque mountain - Ceruti, María Constanza (2022)
In recent decades, there has been an increase in religious tourism to the sanctuaries in the Basque mountains, among which the San Miguel of Aralar stands out for its unique tangible and intangible heritage. Built on the heights of a karst massif lined with chasms and underground caverns, San Miguel Excelsis is a monumental center of Christian pilgrimage adorned with medieval legends of dragons and doomed knights. The ceremonial complex is located below the Altxueta peak, which boasts telecommunications antennas and a sports landmark erected by a local mountaineering club. The author shared with young local devotees the ascent on foot from the Zamartze monastery to the sanctuary on the heights of Aralar, and made a brief solo ascent to the Altxueta summit. In successive visits to the temple of San Miguel, she informally interviewed the custodian sacristan and shepherds who work and live at the foot of the massif. Likewise, she became familiar with various versions of the legend of the Knight Teodosio de Goñi and she observed and documented popular prevention and healing rites through contact with iron chains, and the unusual procedure called “listening to the dragon”.